ANALISIS SPASIAL KEJADIAN STUNTING PADA BALITA DI KOTA DEPOK TAHUN 2020-2022 - Syi'ta Ayatillahi Tumitah (2023)
Stunting is a chronic nutritional disorder in toddlers that affects growth and development so that toddlers look short. Stunting would have an impact on cognitive, motoric, and immune decline. The purpose of this study was to determine the spatial analysis of stunting in toddlers based on risk factors. This research used an ecological study of observational descriptive methods with secondary data from the Health Office & Population and Civil Registration Office of Depok City. The population used analysis units of 63 urban villages in Depok City. Data analysis used spatial autocorrelation with Moran's Index, Moran's Scatterplot, LISA, and BiLISA. The results showed that stunting in Depok City had spatial autocorrelation with a clustering pattern for 3 years. There was spatial autocorrelation between stunting and access to healthy latrines (2022), access to safe drinking water (2021-2022), population density (2020-2022), exclusive breastfeeding (2020-2021), and vitamin A (2020-2022). The conclusion of this study showed that stunting had a clustered pattern, so that monitoring of ownership of healthy latrines, allocating funds for access to drinking water, and socialization related to exclusive breastfeeding and vitamin A could be done to reduce the stunting rate in Depok City.